OPTIMASI EFEK ANALGETIK SIRUP EKSTRAK DAUN BELUNTAS (Pluchea Indica (L.) Less.) TERHADAP MENCIT JANTAN PUTIH (Mus Musculus) DENGAN METODE RANGSANG PANAS - Listina, Osie (Usadha, 2022)
Beluntas plants generally grow wild in dry areas and have enormous benefits in treatment such as eliminating body odor, increasing appetite, overcoming pain and reducing fever. Beluntas leaves contain flavonoids which help the process of relieving pain. Pain is an uncomfortable sensory and emotional feeling related to (threatening) tissue damage. This study aimed to determine whether there is an analgesic effect of beluntas leaves extract syrup. This study was experimental using 25 mice which were divided into 5 groups. The negative control group was given aquades, positive control group was given paracetamol, and 3 experimental groups were given beluntas leaves extract syrup, each with a dose of 150mg/kgBB, 300 mg/kgBB, and 600mg/kgBB. Testting of analgesic effect was conducted by giving pain to test animals, in the form of hot stimulus with temperature of 550C. The response of the mice observed was the licking of the feet and or jumping. Observations were made for 1 minute. Observations were made before giving the test substance, and then successively in the 30, 60, 90, and 120 minutes after administration of the test substance. The results showed the number of responses to pain stimuli in the group of mice given beluntas leaves extract syrup began to decline in the 30 minute and continued to give effect in the 60 minute. In the 90th minute the analgesic effect began to decline, but it still showed the analgesic effect.At the second and third concentrations (300mg/kgBW : 600mg/kgBW) syrup of beluntas leaf extract (Pluchea indica (L.) Less.) had the best analgesic effect.